Using PROMIS(®) to create clinically meaningful profiles of nephrotic syndrome patients - Troost, Jonathan P. (Health Psychol, 2019)
OBJECTIVE: Nephrotic syndrome (NS) is a kidney disease known to adversely impact health-related quality of life (HRQOL). Patient-reported outcome (PRO) measures are commonly used to characterize HRQOL and the patient disease experience. This study aims to improve the interpretability and clinical utility of the Patient-Reported Outcomes Measurement Information System(®) (PROMIS(®)) by identifying distinct meaningful HRQOL profiles in children and adults with NS. METHODS: Patients were from two prospective NS cohort studies (PROMIS-II: 121 children; NEPTUNE: 40 children and 219 adults) with data from six PROMIS domains. Latent Profile Analysis was used to identify subgroups of patients based on PROMIS score patterns. A 3-step analysis of latent profile predictors was used to determine how clinical parameters predicted HRQOL profile membership. RESULTS: We identified three HRQOL profiles (Good, Average, and Poor) with strong indicators of membership classification (entropy>0.86). Complete proteinuria remission, reduction in symptoms, and shorter disease duration, were significant predictors of better HRQOL profile membership. CONCLUSIONS: Patients with NS can be classified by HRQOL into clinically meaningful categories. Integrating this approach into clinic may help in the identification of individuals with poor HRQOL will help clinicians better manage their symptoms and researchers study the causes and possible interventions for these patients. PROMIS HRQOL profiles were reproducible in replication cohorts.